La nación clandestina - Sanjinés, Jorge; Sanjinés, Jorge; Quisbert G., Félix (Fundación Grupo Ukamau, 1989)
Sebastián Mamani, a coffin-maker living on the city outskirts, comes back to his native Aymara village -from which he had been driven out some time ago- carrying a big Death mask, with the aim of dying in a dance as a kind of expiation of his sins that were the cause of his exile, and as a way of being reborn in his lost cultural identity. During this trip, he recalls his past. --